Free will, causality, and neuroscience - Feltz, Bernard; Missal, Marcus; Sims, Andrew (Philosopher) (Value inquiry book series, 2020)
Neuroscientists often consider free will to be an illusion. Contrary to this hypothesis, the contributions to this volume show that recent developments in neuroscience can also support the existence of free will. Firstly, the possibility of intentional consciousness is studied. Secondly, Libet's experiments are discussed from this new perspective. Thirdly, the relationship between free will, causality and language is analyzed. This approach suggests that language grants the human brain a possibility to articulate a meaningful personal life. Therefore, human beings can escape strict biological determinism.